Spatiotemporal Discharge Variability of the Doce River in SE Brazil During MIS 6 and 5 - Arndt, Iris; Voigt, Silke; Petschick, Rainer; Hou, Alicia; Raddatz, Jacek; Albuquerque, Ana Luiza S.; Bahr, André (Frontiers in Earth Science, 2022)
The modern precipitation balance in southeastern (SE) Brazil is regulated by the South American Summer Monsoon and threatened by global climate change. On glacial-interglacial timescales, monsoon intensity was strongly controlled by precession-forced changes in insolation. To date, relatively little is known about the spatiotemporal distribution of tropical precipitation in SE Brazil and the resulting variability of fluvial discharge on glacial-interglacial timescales. Here, we present X-ray diffraction-derived mineralogical data for the 150-70 ka period (marine isotope stage (MIS) 6 to MIS 5) from the Doce River basin. This area was sensitive to changes in monsoonal precipitation intensity due to its proximity to the South Atlantic Convergence Zone. The data, obtained from a marine sediment core (M125-55-7) close to the Doce river mouth (20°S), show pronounced changes in the Doce River suspension load's mineralogical composition on glacial-interglacial and precessional timescales. While the ratio of silicates to carbonates displays precession-paced changes, the mineralogical composition of the carbonate-free fraction discriminates between two assemblages which strongly vary between glacial and interglacial time scales, with precession-forced variability only visible in MIS 5. The first assemblage, dominated by high contents of kaolinite and gibbsite, indicates intensified lowland erosion of mature tropical soils. The second one, characterized by higher contents of the well-ordered illite, quartz and albite, points to intensified erosion of immature soils in the upper Doce Basin. High kaolinite contents in the silicate fraction prevailed in late MIS 6 and indicate pronounced lowland soil erosion along a steepened topographic gradient. The illite-rich mineral assemblage was more abundant in MIS 5, particularly during times of high austral summer insolation, indicating strong monsoonal rainfall and intense physical erosion in the upper catchment. When the summer monsoon weakened in times of lower insolation, the mineral assemblage was dominated by kaolinite again, indicative of lower precipitation and runoff in the upper catchment and dominant lowland erosion.